The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4103/0019-509x.84941
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization for hepatocellular carcinoma: Significance of extrahepatic collateral supply

Abstract: Hepatocellular carcinoma having extrahepatic collateral supply requires additional chemoembolization through the collateral to enhance the efficacy of TACE failing which an alternative locoregional therapy of percutaneous ablation may be resorted to.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated the effectiveness of TACE performed through extrahepatic arteries [21] , [22] , [23] , with variable results in terms of tumor response and clinical safety. Similarly, other authors have reported their experiences and techniques for redistributing arterial flow to lesions with EHFAs but aimed to be treated with TARE [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the effectiveness of TACE performed through extrahepatic arteries [21] , [22] , [23] , with variable results in terms of tumor response and clinical safety. Similarly, other authors have reported their experiences and techniques for redistributing arterial flow to lesions with EHFAs but aimed to be treated with TARE [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, ExCA is not a rare finding, particularly in patients already exposed to repeated TACE treatments and when the HCC is large or peripherally located. The awareness of ExCA is of crucial importance because its diagnosis represents the pre-requisite for TACE success [7,20,21,42]. Once established, ExCA itself does not represent an absolute contraindication to TACE, but it requires a careful benefit-risk assessment in each case and considerable technical skill in performing the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Liver parenchyma has a dual blood supply from both portal vein and hepatic artery, but the vascularisation of HCC nodules is derived solely from the arterial system as a result of the high neoangiogenic activity of this tumour. In the vast majority of the cases, HCC is vascularised by branches of the hepatic artery [4,5], although it may happen that some HCC nodules exhibit an abnormal vascularisation from extra-hepatic collateral arteries (ExCAs), even if the hepatic artery is patent [6,7]. This condition, called extra-hepatic feeding, is not uncommon and it has a clinical relevance, mostly because it can compromise the efficacy of the treatment with trans-arterial chemioembolisation (TACE) [7].…”
Section: Introductionmentioning
confidence: 99%
“…53,167,168 HCC having extra-hepatic collateral supply requires additional chemoembolization through the collateral to enhance the efficacy of TACE failing which an alternative loco-regional therapy of percutaneous ablation may be resorted to. 169 There is no available evidence regarding the choice of chemotherapeutic agent, dosage, dilution and the rate of injection. 155 Doxorubicin, mitomycin and cisplatin are the common chemotherapeutic drugs used alone or in combination.…”
Section: Role Of Trans-catheter Therapies In Hepatocellular Carcinomamentioning
confidence: 99%